Evaluation of early weight loss thresholds for identifying nonresponders to an intensive lifestyle intervention. (28th April 2014) - Unick, Jessica L.; Hogan, Patricia E.; Neiberg, Rebecca H.; Cheskin, Lawrence J.; Dutton, Gareth R.; Evans‐Hudnall, Gina; Jeffery, Robert; Kitabchi, Abbas E.; Nelson, Julie A.; Pi‐Sunyer, F. Xavier; West, Delia Smith; Wing, Rena R.; et al.
<x xml:space="preserve">Abstract</x> Objective Weight losses in lifestyle interventions are variable, yet prediction of long‐term success is difficult. The utility of using various weight loss thresholds in the first 2 months of treatment for predicting 1‐year outcomes was examined. Methods Participants included 2327 adults with type 2 diabetes (BMI:35.8 ± 6.0) randomized to the intensive lifestyle intervention (ILI) of the Look AHEAD trial. ILI included weekly behavioral sessions designed to increase physical activity and reduce caloric intake. 1‐month, 2‐month, and 1‐year weight changes were calculated. Results Participants failing to achieve a ≥2% weight loss at Month 1 were 5.6 (95% CI:4.5, 7.0) times more likely to also not achieve a ≥10% weight loss at Year 1, compared to those losing ≥2% initially. These odds were increased to 11.6 (95% CI:8.6, 15.6) when using a 3% weight loss threshold at Month 2. Only 15.2% and 8.2% of individuals failing to achieve the ≥2% and ≥3% thresholds at Months 1 and 2, respectively, go on to achieve a ≥10% weight loss at Year 1. Conclusions Given the association between initial and 1‐year weight loss, the first few months of treatment may be an opportune time to identify those who are unsuccessful and utilize rescue efforts. Trial Registration clinicaltrials.gov Identifier: NCT00017953